Nonlinear association between TyG-related Indices and motoric cognitive risk syndrome in depressive individuals: evidence from the CHARLS study - Wei, Ze-kun; Li, Cun-yang; Liu, Zhi-yun; Wang, Bo-lin; Wang, Can; Liu, Yang; Ba, Te-jin; Kong, Li; Zhang, Fei-hu (Frontiers in Psychiatry, 2025)
BackgroundMotoric Cognitive Risk Syndrome (MCR), defined by cognitive complaints and slow gait, is a pre-dementia condition linked to metabolic dysfunction. The triglyceride-glucose (TyG) index and its composite derivatives are surrogate markers of insulin resistance and may contribute to cognitive decline. This study investigated the associations between TyG-related indices and MCR risk in middle-aged and older adults with depressive symptoms, focusing on nonlinear relationships and subgroup modifications.MethodsThis study included 5,657 participants aged ≥45 years from the China Health and Retirement Longitudinal Study (CHARLS). Associations between four TyG-related indices (TyG, TyG-BMI, TyG-WC, TyG-WHtR) and MCR were assessed using logistic regression. Nonlinear associations were examined via generalized additive models and two-piecewise linear regression. Stratified analyses explored effect modifications by age, sex, education, and depressive status.ResultsAll TyG-related indices were positively associated with MCR. TyG-BMI demonstrated the strongest and most consistent association, with a significant threshold at 276.05. Below this point, MCR risk increased with TyG-BMI (OR = 1.01; 95% CI: 1.004-1.017; P = 0.003), while no association was found above it (P = 0.416). Similar nonlinear trends were observed in depressive individuals. Subgroup analyses indicated stronger associations in older adults (≥60 years).ConclusionTyG-BMI demonstrates a nonlinear association with MCR risk and may serve as an accessible biomarker for early cognitive risk detection in depressive individuals.